Robot Berkaki Kawat Pendeteksi Halangan (Object Detecting Robot With Wire Leg) - Oskar Ika Adi Nugroho (Media Aplikom, 2010)
In recent years, robots have captured the interest of more and more people. In the entertainment industry , robot has been developed in various style. One of it is robot that have shape and behavior like insect. Based on that reason, writer wants to make a robot that has a unique form. This kind of robot have a creative and imaginative design , of course it is supported by appropriate capability. This robot also have ability to calculate distance and avoid an obstacle that required by robot which works in frequently disturbed path. Range Detector Wire Leg Robot Base on AT89S51 use infrared detector as distance and obstacle detector. As infrared receiver used an infrared module GP1U52X . The range between the obstacle and robot is gotten by measuring the strength of the reflected burst of infrared light. The result of distance measurement is used by microcontroller to decide direction of robot movement. DC motor used to move the robot for DC motor driver used L293D IC’s. The research shows that wire leg robot can detect obstacle distance in front of it based on strength of the infrared reflected burst (near , medium and far distance) . From that detection result, wire leg robot can make movement to avoid the obstacle. Object used as an distance detector reference must not have slippery surface / flat